Qualidade de silagens de trigo e milho e desempenho de novilhos confinados - Oliveira, Marcos Rogério (2014)
The effects of inoculation on the nutritional value, standard fermentation, aerobic stability and dry matter losses (DM) in wheat silages evaluated in three stratum in large-scale silos. The homolactic inoculated silage wheat reduces the total DM losses during storage and modifies the fermentation pattern, with reduced aerobic stability of silage. The use of the base homolacts inoculant alters the fermentation characteristics and aerobic stability of silage in the stratum of wheat. The degradability of wheat silages with or without the use of inoculant (Lactobacillus plantarum and Pediococcus acidilactici), and conventional or transgenic silage corn (Bacillus thuringiensis). The treatments consisted of wheat silage (SW), wheat silage inoculant (WSI), conventional corn silage (CCS) and transgenic maize silage (GMCS). The corn silage had lower fraction (I) and higher NDF degradability compared to silages wheat. The inoculation reduces the degradability of DM and fiber. The addition of the modified gene results in greater degradation of DM. The performance of feedlot steers 24 Charolais x Nellore crosses fed with diets that included wheat silage (WS), wheat silage with homolactic inoculant (WSI) and corn silage (CS). This provides better corn silage intake, digestibility and animal response, relative to wheat silage. The use of bacterial inoculants on silage, wheat has no effect on the performance of feedlot steers.